PEMODELAN PARAMETER α HIDROGRAF SATUAN SINTETIK NAKAYASU DAS JANEBERANG - Acep Hidayat (Universitas Trisakti, 2022)
With the limited availability of hydrograph data, it becomes an obstacle for water building planning. This obstacle makes HSS models provide considerable benefits for water building planning. Ideally, each watershed (DAS) has a Unit Hydrograph with its own characteristics. This research was conducted with the aim of observing the hydrograph characteristics of observations in each watershed and all watersheds in the province of South Sulawesi. This study was conducted to model the Alpha equation with the influence parameters of watershed area (A), river length (L), riverbed slope (S), Form factor (FD) and time concentration (tg). With the Watershed Form Factor it has an influence on the Alpha value so it is very helpful in planning water structures. The modeling analysis used is nonlinear regression because it has different data variants based on the homogeneity test carried out. It is hoped that the resulting Alpha value can match the real conditions in the environment so that it will have an impact on a more efficient design.